Factors affecting mortality in COVID-19-associated pulmonary aspergillosis: An international ID-IRI study - Sahin, Meyha; Yilmaz, Mesut; Mert, Ali; Emecen, Ahmet Naci; Rahman S. Al Maslamani, Muna A.; Mahmoud A. Hashim, Samar; Ittaman, Ajithkumar Valooparambil; Wadi Al Ramahi, Jamal; Gergely Szabo, Balint; Konopnicki, Deborah; Baskol Elik, Dilsah; Lakatos, Botond; et al. (Heliyon, 2024)
This study aimed to identify factors that influence the mortality rate of patients with coronavirus disease (COVID-19)-associated pulmonary aspergillosis (CAPA). In this cross-sectional study, data from 23 centers across 15 countries, spanning the period of March 2020 to December 2021, were retrospectively collected. The study population comprised patients who developed invasive pulmonary aspergillosis while being treated for COVID-19 in the intensive care unit. Cox regression and decision tree analyses were used to identify factors associated with mortality in patients with CAPA. A total of 162 patients (males, 65.4 %; median age: 64 [25th–75th: 54.0–73.8] years) were included in the study, of whom 113 died during the 90-day follow-up period. The median duration from CAPA diagnosis to death was 12 (25th–75th: 7–19) days. In the multivariable Cox regression model, an age of ≥65 years (hazard ratio [HR]: 2.05, 95 % confidence interval [CI]: 1.37–3.07), requiring vasopressor therapy at the time of CAPA diagnosis (HR: 1.80, 95 % CI: 1.17–2.76), and receiving renal replacement therapy at the time of CAPA diagnosis (HR: 2.27, 95 % CI: 1.35–3.82) were identified as predictors of mortality. Decision tree analysis revealed that patients with CAPA aged ≥65 years who received corticosteroid treatment for COVID-19 displayed higher mortality rates (estimated rate: 1.6, observed in 46 % of patients). This study concluded that elderly patients with CAPA who receive corticosteroids are at a significantly higher risk of mortality, particularly if they experience multiorgan failure.